INFESTAÃ‡ÃƒO DE COLEOBROCAS EM MADEIRAS DE Eucalyptus spp. EM CUIABÃ, ESTADO DE MATO GROSSO - Dorval, Alberto; Peres Filho, OtÃ¡vio; Marques, Eli Nunes; Berti Filho, Evoneo; Moura, RogÃ©rio Goularte (REVISTA DE AGRICULTURA, 2015)
INFESTAÃ‡ÃƒO DE COLEOBROCAS EM MADEIRAS DE Eucalyptus spp. EM CUIABÃ, ESTADO DE MATO GROSSO